Metabolic changes of the acetogen Clostridium sp. AWRP through adaptation to acetate challenge - Kwon, Soo Jae; Lee, Joungmin; Lee, Hyun Sook (Frontiers in Microbiology, 2022)
In this study, we report the phenotypic changes that occurred in the acetogenic bacterium Clostridium sp. AWRP as a result of an adaptive laboratory evolution (ALE) under the acetate challenge. Acetate-adapted strain 46T-a displayed acetate tolerance to acetate up to 10 g L-1 and increased ethanol production in small-scale cultures. The adapted strain showed a higher cell density than AWRP even without exogenous acetate supplementation. 46T-a was shown to have reduced gas consumption rate and metabolite production. It was intriguing to note that 46T-a, unlike AWRP, continued to consume H2 at low CO2 levels. Genome sequencing revealed that the adapted strain harbored three point mutations in the genes encoding an electron-bifurcating hydrogenase (Hyt) crucial for autotrophic growth in CO2 + H2, in addition to one in the dnaK gene. Transcriptome analysis revealed that most genes involved in the CO2-fixation Wood-Ljungdahl pathway and auxiliary pathways for energy conservation (e.g., Rnf complex, Nfn, etc.) were significantly down-regulated in 46T-a. Several metabolic pathways involved in dissimilation of nucleosides and carbohydrates were significantly up-regulated in 46T-a, indicating that 46T-a evolved to utilize organic substrates rather than CO2 + H2. Further investigation into degeneration in carbon fixation of the acetate-adapted strain will provide practical implications for CO2 + H2 fermentation using acetogenic bacteria for long-term continuous fermentation.